Basic Hindi I - Ranjan, Rajiv (Open textbook library., 2021)
Basic Hindi I is an online, interactive, and tech-enhanced textbook that promotes speaking, listening, reading, writing, and cultural skills. Each Chapter in this book has clear stated learning outcomes, a review of previous chapters, reading/listening sections, study abroad section, relevant grammatical items, and cultural notes. The pedagogical approach in the book is mixed and informed by the socio-cultural approaches and the generative approaches of the Second Language Acquisition theory. The mixed theoretical backgrounds match diverse learning and teaching philosophies and styles. Following the learning outcomes guided by American Council of Teaching Foreign Language (ACTFL), this textbook aims for the novice learners to attain intermediate low to mid-level proficiency level. The textbook incorporates pictures, audio-visual materials, and activities developed on the H5P platform to keep learners engaged.